CHARAK SAMHITA: A TEXTBOOK OF ANCIENT RESEARCH METHODOLOGY (International Journal of Ayurveda and Pharma Research, 2016)
Charak Samhita is the one of the identities of Ayurveda. To carry out any research, one needs to draw certain methodology, some kind of line of action. Charak Samhita shows us the path on that way. By studying Charak Samhita in a view to understand its research methodology, one finds it a textbook of Ancient Research Methodology itself. The method of precipitating a principle, methods of proving it i.e. Panchavayavi Vakya are studied here. Use of interrogation as a tool of collection of knowledge, importance of animal study is also discussed here. Sample size determination, minimal standard size, precipitation of higher and lower values, estimation of the best and the worst are mentioned in this topic. Tantrayukti to understand any science and Vadmargapade to prove ones view is also mentioned. Study of epidemiology, types of examinations with their limitations, cause effect relationship is also mentioned here. Thus it finds Charak Samhita as a very scientifically bound textbook.